PENGARUH BUDAYA SEKOLAH, FASILITAS MENGAJAR, MOTIVASI, DAN KEPUASAN KERJA TERHADAP KINERJA GURU DI SEKOLAH DASAR (SD) NEGERI SE-GUGUS I KECAMATAN STABAT KABUPATEN LANGKAT - Baheramsyah . (Manajemen dan Bisnis, 2020)
The formulation in this research is whether school culture, teaching facilities, motivation and job satisfaction simultaneously affect the performance of teachers in the elementary School (SD) of cluster state I Se-District Stabat, Langkat District, and the purpose of this research is to know and analyze whether school culture, teaching facilities, motivation and work satisfaction simultaneously affect the performance of teachers in the elementary School (SD) state cluster I Se-District Stabat, Langkat District. This research is a quantitative descriptive study. Data collection techniques are conducted through interviews, questionaire questions and documentation studies. Sample in this study as many as 76 teachers at elementary School (SD) Negeri cluster I Se-District Stabat district of Langkat. Variables are measured at Likert scale.  Hypothesis testing using multiple linear regression analyses through F-test and T-Test. The results of the test in unison showed that the variables of the school culture, work facilities and motivation and job satisfaction as a free variable (X) have significant effect on the teachers ' performance variables of the state elementary School cluster I Se-District Stabat District, Langkat. Partially, the school culture has no effect on the state teachers ' performance of cluster I Se-District Stabat, Langkat District. Furthermore, the work facility has a positive and significant effect on the state elementary school teachers cluster I Se-district Stabat in Langkat District. The motivation has positive and significant impact on the state elementary school teachers cluster I Se-district Stabat in Langkat District.  Job satisfaction positively and significantly affect the teacher's performance of State Elementary school cluster I Se-District Stabat Langkat District